Processing and Interpretation of Multichannel Seismic Reflection Data Acquired off Isfjorden, Svalbard - Dincturk, Guney (The University of Bergen, 2023)
The Svalbard archipelago has been complexly deformed during its billions of years-long evolution history, where fault zones, other deformation structures and hard seafloor morphology have emerged. This research project has aimed to characterize the main geological structures in the study area located on the western shelf of Spitsbergen by processing and interpreting of four 2D marine seismic reflection profiles. The quality of the seismic data has been influenced by several sorts of noise, dominantly surface-related multiples due to the hard seafloor in the study area, where the velocities of primary waves are approximately 5500 m/s and often escalate up to 6500 m/s at shallow depths. A total of five different processing workflows have been applied to a seismic profile in order to remove the multiples from the data. The multiple extraction & adaptive subtraction approach has been determined as the most effective remedy for multiple attenuation among the tested methods, as it enhanced the signal-to-noise ratio the most. Thanks to that approach, and many other essential processing sequences, including post-stack time migration in the main workflow, the seismic datasets have become almost multiple-free. Seismic interpretation of the four processed profiles has been done to distinguish the main geological setting in the study area. Nine seismic horizons interpreted between the seabed and basement, as well as several major faults, allowed the division into five stratigraphic units, being the Quaternary, Cenozoic, Mesozoic-Paleozoic, Devonian sedimentary successions and the crystalline basement (so-called Hecla Hoek). The thickness and 2D - 3D surface maps including faults have supported the identification of the main structures in the study area: the Hornsund Fault Zone and a Devonian Graben. The interpretation implies a new model describing the development of a N-S trending fault-bounded rift basin, named Devonian Graben structure, as a product of the collapsed Caledonian mountain range due to continental ...